Distribusi Spasial Kepadatan Penduduk dan Jumlah Kejadian Covid-19 Mingguan di Kabupaten Magelang - Sidiq Purwoko; Widya Hary Cahyati; Zainuddin Zainuddin; Ina Kusrini (Poltekkes Kemenkes Padang, 2021)
Covid-19 is a deadly infectious disease with a fast transmission rate in a short time. The incidence of Covid-19 is caused by various factors, one of which is the demographic factor of an area. In 2020, positive Confirmation Cases in Magelang Regency were ranked the second highest in Central Java Province with 4418 cases. . This type of quantitative descriptive research with an ecological study design uses a spatial approach with a sub-district analysis unit. The sample in the study was all new cases of positive confirmation of Covid-19 in the next episode in December 2020 by utilizing secondary data on the official website of the Magelang Regency government. The analysis used is correlation and regression analysis between variables, while the mapping of cases uses an overlay technique using QGIS 3.10 software. The results showed a strong relationship between variables by 54% and from the results of spatial mapping showed the highest cases occurred in the third week with 790 cases and the two highest sub-districts were sub-districts with population density above 1900 people/km2, namely Mertoyudan District and Mungkid District. The conclusion of the study is that the distribution of the Covid-19 television program in Magelang Regency in December 2020 is influenced by the level of population density. Research advice is that stakeholders' attention is needed for areas with high density levels in handling Covid-19 in Magelang Regency.